PENGEMBANGAN BAHAN AJAR DALAM BENTUK MEDIA KOMIK DENGAN ADOBE PHOTOSHOP CS6 PADA MATERI LAJU REAKSI - Minarni, Minarni (Universitas Negeri Semarang, 2020)
In achieving the learning objectives, many components are involved including teaching materials. One of the teaching materials that will be developed in the form of printed teaching materials, namely comics. The role of comics has a very important role because the emotional involvement of the reader will greatly affect the memory and memory of the subject matter obtained. This study aims to develop the teaching materials in the form of comic media using Adobe Photoshop CS6 software on the reaction rate material to determine teacher ratings and student responses to the developed comic media. This study uses a learning design procedural development model from ADDIE. The research instruments used were interview guidelines, needs questionnaires, expert team validation questionnaires, assessment questionnaires and student response questionnaires. The product of the development was validated by the content and construct validation team (Content Validity and Construct Validity), and was assessed by an expert validator in the multimedia field and then tested on a small group, the data obtained was further analyzed descriptively-quantitative. The positive result of class XI IPA 2 student responses at SMA N 7 Sarolangun were 87.02%, the results obtained that this comic media is very good and interesting. Based on the process and results of media development as well as material and results, overall it is concluded that this comic media product is feasible and interesting to use.Ã‚Â